Clinical Redesign: An Innovative Approach to Leading Change at an Academic Healthcare System. Issue 1 (January 2022) - Li, Luming; Davis, Melissa; Kim, Nancy; Lipka, Susan; Branson, Brittany; Amport, Stephanie; Schwartz, Ian; Sussman, Scott
Abstract : Supplemental Digital Content is available in the text Abstract : SUMMARY: Goal: We characterized the core elements of a clinical redesign program (CRDP) to represent both a team and a methodology to rapidly improve outcomes important to patients and hospitals (e.g., length of stay, unnecessary care, and cost). Unique features of our CRDP included a clinician lead, engagement from senior leadership, formal project management, and rapid cycle implementation. We aimed to examine the effectiveness of this strategy across three different project examples. Methods: Using an observational pre–post study design, we compared the patient-level data for three representative projects applying the core elements of the CRDP: (1) optimizing telemetry utilization, (2) creating a high flow nasal cannula protocol in the pediatric intensive care unit, and (3) standardizing care for patients with chronic obstructive pulmonary disease and pneumonia. Principal Findings: The primary metrics for all three projects were a project-specific clinical outcome and cost per case. Telemetry utilization was reduced from a peak of 26.0% to 19.6% with a 1, 075 reduction in cost per case. Creation of a high flow nasal cannula protocol led to a decrease in median pediatric intensive care unit length of stay from 77.3 to 75.8 hours with a 2, 020 decrease in cost per case. Decreasing variation of care for patients with chronic obstructive pulmonary disease and pneumonia diagnoses led to a 371 decrease in cost per case. Applications to Practice: The CRDP adds to existing clinical quality improvement models using a structured process for a 90-day rapid cycle project turnaround. In addition, the CRDP incorporates project management and defined team members for the completion and sustainability of projects. The CRDP also facilitates the scalable translation of projects from local to systemwide and incorporates tracking of clinical and financial outcomes through interval internal auditing. These elements provide prioritization, resource allocation, and expertise for improved patient care and high-value care delivery. The CRDP can be adapted for other contexts to lead and foster momentum and drive rapid and successful completion of clinical improvement projects.